Benign and Malignant Proliferative Fibro-osseous and Osseous Lesions of the Oral Cavity of Dogs. (September 2015) - Soltero-Rivera, M.; Engiles, J. B.; Reiter, A. M.; Reetz, J.; Lewis, J. R.; Sánchez, M. D.
Ossifying fibroma (OF) and fibrous dysplasia (FD) are benign, intraosseous, proliferative fibro-osseous lesions (PFOLs) characterized by replacement of normal bone by a fibrous matrix with various degrees of mineralization and ossification. Osteomas are benign tumors composed of mature, well-differentiated bone. Clinical, imaging, and histologic features of 15 initially diagnosed benign PFOLs and osteomas of the canine oral cavity were evaluated. Final diagnoses after reevaluation were as follows: OF (3 cases), FD (4 cases), low-grade osteosarcoma (LG-OSA) (3 cases), and osteoma (5 cases). Histology alone often did not result in a definitive diagnosis for PFOL. OF appeared as a well-circumscribed, radiopaque mass with some degree of bone lysis on imaging. Most lesions of FD showed soft tissue opacity with bone lysis and ill-defined margins. Low-grade OSA appeared as a lytic lesion with a mixed opacity and ill-defined margins. Osteomas were characterized by a mineralized, expansile, well-circumscribed lesion. Although histologic features of PFOLs were typically bland, the lesions diagnosed as LG-OSA had some features of malignancy (eg, bone invasion or a higher mitotic index). Treatment varied widely. Of the 10 dogs with benign PFOL or osteoma with known outcome (10/12), 9 showed either complete response (6/10) or stable disease (3/10) after treatment. Of the 2 dogs with LG-OSA with known outcome, 1 showed complete response after curative intent surgery, but 1 patient had recurrence after partial maxillectomy. Definitive diagnosis of mandibular/maxillary PFOL is challenging via histopathologic examination alone, and accurate diagnosis is best achieved through assimilation of clinical, imaging, and histopathologic features.